DETECTION OF PARVOVIRUS B19 IN BAD OBSTETRIC HISTORY BY USING REAL TIME PCR (Iraqi Journal of Medical Sciences, 2018)
Background: Human parvovirus B19 (B19V) is a small single-stranded DNA virus. Infection during pregnancy can cause a variety of signs of fetal damage. The risk of adverse fetal outcome is increased if maternal infection occurs during the first two trimesters of pregnancy but may also happen during the third trimester.Objective: to determine the screen of parvovirus B19 in pregnant women with bad obstetric history by real time polymerase chain reaction (PCR).Methods: Two hundred Plasma and 200 placental tissue samples were collected from all pregnant women enrolled in this study. Three ml whole blood was collected in sterile EDTA-blood tube. Plasma was obtained by centrifugation of whole blood. Twenty-five grams of the placental tissue was homogenized with 10 ml of PBS by using tissue homogenizer for about 1 min at 4 °C. Results: 40 (20%) out of 200 plasma samples were real time PCR positive, the remainder 160 (80%) were real time PCR negative. Nineteen (9.5%) out of 200 placental tissue samples were positive for B19 real time PCR the remainder 181 (90.5 %) were real time PCR negative. All placental tissue positive (n=19) were positive by real- time PCR in plasma samples (n=40). Out of 40 pregnant women presented with positive parvoviruses results in current study demonstrated 21 (52.5%) gave abortion in first trimester and only 8 (20%) gave abortion in second trimester.Conclusion: Parvovirus B19 is common and highly distributed among pregnant ladies in this study and there is a significant association between B19 positivity and adverse pregnancy outcome.Keywords: Parvovirus B19, bad obstetric history, adverse pregnancy outcome, non-immune hydrops fetalisCitation: Abdulhassan LF, Hathal HD, Abdullah TH. Detection of Parvovirus B19 in bad obstetric history by using Real Time PCR. Iraqi JMS. 2017; Vol. 15(4): 350-357. doi: 10.22578/IJMS.15.4.5
Keywords: Parvovirus B19; bad obstetric history; adverse pregnancy outcome; nonimmune hydrops fetalis